Prognostic factors for relapse in patients with clinical stage I testicular cancer: protocol for a Danish nationwide cohort study - Wagner, Thomas (BMJ Open, 2019)
INTRODUCTION: Approximately one-fourth of patients with clinical stage I testicular germ cell cancer will relapse within 5 years of follow-up. Certain histopathological features in the primary tumour have been associated with an increased risk of relapse. The available evidence on the prognostic value of the risk factors, however, is hampered by heterogeneity of the study populations included and variable reporting of the histopathological features. The aim of this study is to identify pathological risk factors for relapse in an unselected large nationwide cohort of patients with stage I disease. METHODS AND ANALYSIS: All incident cases of stage I testicular germ cell cancer diagnosed in Denmark between 2013 and 2018 will be identified using the nationwide prospective Danish Testicular Cancer (DaTeCa) database. Archived microscopic slides from the orchiectomy specimens will be retrieved through linkage to the Danish Pathology Data Bank and reviewed blinded to the clinical outcome. The DaTeCa database includes 960 stage I seminoma patients with expected 185 relapses and 480 patients with stage I non-seminoma with expected 150 relapses. A minimum follow-up period of 3 years of all patients will be ensured. Predefined prognostic variables will be investigated with regard to relapse in univariable and multivariable analysis using the Cox proportional hazards model. ETHICS AND DISSEMINATION: This study protocol has been approved by the Regional Ethics Committee (Region Zealand, Denmark) and the Danish Data Protection Agency. All data will be managed confidentially according to legislation. Study results will be presented at international conferences and published in peer-review journals.